Asselian–Sakmarian brachiopod zonation of the left bank of the lower reaches of the Lena River, Northeast Russia - V.I. Makoshin; R.V. Kutygin (Учёные записки Казанского университета: Серия Естественные науки)
This article summarizes the results of our study of the Early Permian brachiopods collected 5.9–6.3 km northwest of the village of Chekurovka that were used to develop the first biostratigraphic zonation of the Asselian–Sakmarian deposits on the left bank of the lower reaches of the Lena River. At the base of the Permian section, the Jakutoproductus lenensis Beds were identified. They are overlain by the Jakutoproductus insignis Zone with numerous shells of the index species. The Jakutoproductus terechovi and Jakutoproductus rugosus Zones, which are characterized by index species, occur even higher in the section. The boundary between the Khorokytian and Echian Regional Stages is defined by the first occurrence of J. insignis at the base of the Insignis Zone. The identified zonal sequence is identical to the previously studied Kubalakh section on the right bank of the lower reaches of the Lena River. However, the thickness of the biostratigraphic zones on the left bank is reduced by half, and a significant lower part of the Khorokytian Regional Stage (below the Lenensis Beds) is missing because it falls on the stratigraphic break between the Cambrian and Permian deposits. The zonation performed shows that there is a direct correlation between the Chekurovka section and the Asselian–Sakmarian deposits of Western Verkhoyanie and the Omolon Massif due to common index species of the biostratigraphic units.